OTU-027 A study of post colonoscopy colorectal cancer (PCCRC) in england. (8th June 2018) - Burr, Nicholas; Rutter, Matthew; Shelton, Jon; Smith, Andy; Pearson, Clare; Morris, Eva; Valori, Roland
Abstract : Introduction: PCCRC is a key quality indicator for the detection and prevention of colorectal adenocarcinoma (CRC). It is not known whether rates of PCCRC are changing over time. There is limited evidence of factors associated with PCCRC that might be amenable to quality improvement interventions. This study investigated trends in rates of PCCRC in the NHS in England; the extent of variation between NHS trusts; and potential causal associations with PCCRC. Methods: Using linked national Hospital Episode Statistics and National Cancer Registration and Analysis Service data all individuals who had undergone a colonoscopy procedure between 1/1/2006 and 31/12/2012 and who developed a CRC to 31/12/2015 were identified. NHS trust provider status and potential associations with PCCRC were included in the analysis. International consensus methodology was used to calculate the PCCRC – 3 year rate (PCCRC-3 yr). 1 2 Colonoscopies were labelled as true positive (CRC within 0 to 6 months of the procedure), false negative (CRC within 6 to 36 months) and true negative (CRC beyond 36 months). The PCCRC-3 yr rate was calculated as: false negatives/(true positive +false negative) x 100%. The PCCRC-3 yr rate was calculated for each year from 2006 to 2012. In addition, the rate in each colonoscopy provider was calculated, and organisations grouped using quintiles. PCCRC rates were calculated in relation to patient and tumour characteristics. Results: Between 2006 and 2012 1 08 908 colonoscopies followed by a diagnosis of CRC were identified. Of these, 93 240 (86%) were labelled true positive, 7781 (7%) were false negatives, and 7887 (7%) were true negative tests. There was a significant reduction in PCCRC-3 yr rates, from 8.6% in 2006 to 7.5% in 2012 (Chi 2 for trend p<0.01). There was variation in unadjusted, mean PCCRC-3 yr rate between NHS Trusts from 5% (SD ±2%) in the highest performing quintile to 11% (SD ±2%) in the lowest. PCCRCs were significantly associated with female sex, right-sided colonic lesions, inflammatory bowel disease and diverticular disease diagnosis, mucinous CRC and in individuals with metachronous CRC. Conclusion: There has been a significant reduction in PCCRC-3 yr rates from 2006 to 2012, likely to be related to improvements in colonoscopic quality: particularly improved caecal intubation and bowel preparation resulting in improved lesion recognition and removal. There appears to be unwarranted variation of PCCRC-3 yr rates across NHS trusts. Reasons for this variation need to be explored and subject to quality improvement projects. Evidence from this study can be used to help target those at highest risk of PCCRC. References: . Morris EJA, et al. Gut2014;64:1248–56. . Beintaris I, et al. UEG J 2017;5:PO436.